The Impact of Tourism Management on Firm Performance: Chiang Mai Tourism Industry Perspective - JANGKRAJARNG, Varattaya; CHERNBUMROONG, Sainatee; CHERAPANUKORN, Vimolboon (Journal of Environmental Management and Tourism; Vol 13 No 8 (2022): JEMT, Volume XIII, Issue 8(64), Winter 2022, 2022)
Due to the important of tourism industry, the entrepreneurs in tourism supply chain should concern about information sharing in order to increase service quality and the firm performance. However, there is limited study focusing on the impact of information sharing factor toward firm performance especially in tourism sector. This research aims to examined the consistency of structural equation modelling of an impact of information sharing on firm performance for tourism industry. Questionnaires were distributed to 280 participants in tourism industry in Chiang Mai, Thailand. Data were analysed by the analysis of CFA and SEM via LISREL 8.54. The structural equation modelling in information sharing and the performance of tourism industry in Chiang Mai were consistent with empirical data (χ²/df = 2.10, GFI = 0.88, AGFI = 0.98, RMSEA = 0.03, PCLOSE = 0.98, NFI = 0.98, IFI = 0.99 and CFI = 0.97). The SEM results presents that information sharing factor is positively relationship with tourism supply chain, service quality and firm performance variables. Also, Service quality is significant positive impact on Firm performance through information sharing at 0.01. Therefore, tourism supply chain and service quality with considering on information sharing can lead to the increasing of the firm performance.